THE MANAGEMENT OF LIMITED MANDIBULAR MOVEMENT CAUSED BY CONDYLAR FRACTURE WITH REPOSITIONING SPLINT - Ira Tanti; Laura Susanti Himawan (Faculty of Dentistry, Universitas Indonesia, 2015)
Fractures of the neck of condyle usually are the result of a blow to the mandible. A lateral blow to the body of the mandible commonly causes a contralateral condyle fracture. There are many signs and symptoms of a condylar fracture, for example crepitation, deviation of the mandible to the side of injury, and spasm of the associated group of muscles. These will result in a functional disability, which is usually seen as a limited mandibular movement. This paper reported a patient with a fracture of the condylar neck. Patient had been treated with closed reduction and immobilization for 2 months. After that, she felt that her bite was changed, she could not occlude her teeth well, and she had clicking sound in the right joint when she opened her mouth. Besides that, patient had difficulties to move the mandible to the left side, and she could not open her mouth widely. The patient was treated with a repositioning splint and she had to do some jaw exercises. The purposes were to regain the position of condyle, to reduce the muscle spasm and finally got the normal jaw movement.